Surgical site infection and its risk factors in colon surgeries - Benato Fusco, Suzimar de Fatima [UNESP]; Massarico, Natiara Medolago [UNESP]; Faria Fadul Alves, Maria Virginia Martins [UNESP]; Castelo Branco Fortaleza, Carlos Magno [UNESP]; Pereira Pavan, Erika Cibele [UNESP]; Palhares, Valeria de Castilho [UNESP]; Melo, Carlos Eduardo de [UNESP]; Garcia de Avila, Marla Andreia [UNESP]; Trevizani Nitsche, Maria Jose [UNESP] (Univ Sao Paolo, 2016)
Objective: To identify the occurrence of surgical site infection (SSI) and its risk factors in patients undergoing colon surgery in a tertiary hospital located in the countryside of the state of Sao Paulo. Method: Retrospective cohort study, with collection of information contained in the medical records of patients undergoing colon surgery in the period between January 2010 and December 2013. The studied variables were the possible risk factors related to the patient, to demographic characteristics and the surgical procedure. Results: In total, were evaluated 155 patients with an overall SSI incidence of 16.7%. A statistically significant association was found both in the univariate as in the multivariate analysis between the SSI and the following variables: male gender, Charlson index and mechanical bowel preparation. Conclusion: The understanding of health professionals about the factors that influence the incidence of SSI in colon surgery may contribute to the quality of care provided to surgical patients, from effective actions to minimize the risk of infections.
Keywords: Surgical Wound Infection; Colorectal Surgery; Perioperative Nursing